Acuyoga Intervention: A Promising Approach to Combat Obesity in Adolescent Girls - Evidence from a Quasi-Experimental Study" - Khuzaifah; Sri Sumarni; Marsum (Jurnal Bidan Cerdas, 2024)
Background : Obesity is an imbalance between food intake and the amount of energy used during daily activities. RI Health Data for 2017 recorded 153,705 cases of death due to obesity found in the age group of adolescents and young adults. There is still a lack of optimizing the government's efforts in handling obesity cases so there is a need for new innovations that can help reduce the incidence of obesity, especially in young women. This study aims to determine the effectiveness of acuyoga on body mass index and abdominal circumference of obese female adolescents Materials and Methods: This study was a quasi-experimental study with a one group design pretest posttest research conducted during February-March 2023. The sampling method for this study was purposive sampling with a total sample of 30 people. Results: Obtained an average difference in body mass index before and after being given acuyoga of 0.01 (p=0.000) and abdominal circumference of 1.20 (p=0.000) Conclusion: Acuyoga is effective in reducing body mass index and abdominal circumference in obese female adolescents